Pembuatan Abstrak Informatif Hasil Penelitian Dosen di Perpustakaan Fakultas Kedokteran Universitas Andalas - Oktari, Mutia Zikro; Rahmah, Elva (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
AbstractÂ This paper discussed about the creation of informative abstracts of research lecturer at Andalas University Library. This study aims to depict or describe the design process of informative abstracts of the research faculty at the Library of the Faculty of Medicine, University of Andalas. Data were collected through direct observation to the field with a descriptive method of observing the ongoing events during the study. Stages of making informative abstracts are: (1) selecting and collecting abstract; (2) understand and record important information contained in the abstract; (3) typing abstracts (4) make abstract; (5) prepare abstracts and indexes make. This set of informative abstracts compiled by author in a research report or research lecturer at the Library of the Faculty of Medicine, University of Andalas. In the abstract also be made subject index, author index and keyword index.Keyword: informative, research, lecturer